1977
DOI: 10.1136/bmj.1.6077.1626
|View full text |Cite
|
Sign up to set email alerts
|

Sequential treatment with quinine and mefloquine or quinine and pyrimethamine-sulfadoxine for falciparum malaria.

Abstract: SummaryPatients with falciparum malaria were studied in Thailapd, an area of known chloroquine resistance. The patients were unselected and some had severe malaria, and they were randomly assigned to one of two sequential regimens. A short course of quinine (average 4 doses, equivalent to 2 g base) followed by a single dose of pyrimethamine-sulfadoxine (Fansidar) cured 92% of patients (36 out of 39), while a short course of quinine followed by a single 1-5-g dose of mefloquine cured all of the 35 patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…erythro-«-piperidyl-2,8-bis-(trifluoromethyl)4-quinoline methanol hydro chloride], was found to be highly active against various forms of animal and human malarial infections [1][2][3][4][5]. An extended clini cal trial conducted in Thailand by the Walter Reed Army Institute of Research in Wash ington (WRAIR) indicated that the drug may also control forms of Plasmodium falciparum which have become resistant to chloroquinc [6][7][8]. Therefore, the WHO decided to give top priority to the develop ment of this drug as a new promising antimalarial.…”
Section: Introductionmentioning
confidence: 99%
“…erythro-«-piperidyl-2,8-bis-(trifluoromethyl)4-quinoline methanol hydro chloride], was found to be highly active against various forms of animal and human malarial infections [1][2][3][4][5]. An extended clini cal trial conducted in Thailand by the Walter Reed Army Institute of Research in Wash ington (WRAIR) indicated that the drug may also control forms of Plasmodium falciparum which have become resistant to chloroquinc [6][7][8]. Therefore, the WHO decided to give top priority to the develop ment of this drug as a new promising antimalarial.…”
Section: Introductionmentioning
confidence: 99%
“…Some trials have reported high efficacy of quinine plus SP [16][17][18]26]. A cure rate of 92-96% was achieved in Thai adults [16,17] and a cure rate of 92% in Brazilian adults [26].…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, SP is often added at discharge. This regimen has been shown to be effective in Thailand [16,17]. In Africa, where the practice seems widespread, it has been assessed in only two trials: in South Africa, an area with low levels of SP resistance, the short course of quinine therapy plus a single dose of SP for the treatment of non-severe hospitalized children was highly effective, with a cure rate of 99% [18]; in Kenya (East Africa), an area with high levels of SP resistance, a failure rate of 13.9% has been reported in children with severe falciparum malaria [19].…”
Section: Introductionmentioning
confidence: 98%
“…Consequently, chloroquine resistance in this model may be attributed to reduced exposure of the parasites rather than to ineffectiveness of the drug after it reaches the parasites: This mechanism of resistance provides a basis for explaining how drugs in the same chemotherapeutic class with chloroquine could be effective in the treatment of chloroquine-resistant malaria. For example, amodiaquine, quinine, and mefloquine might have exactly the same, albeit unknown, mechanism of action as chloroquine (2) and yet be more effective in the treatment of chloroquine-resistant malaria (1,13,(16)(17)(18)(19)(20)(21) because they penetrate to the parasites. These four drugs all are quinoline derivatives and have many characteristics in common, but they also possess t Contribution 1521 from the Army Research Program on malaria.…”
mentioning
confidence: 99%
“…We now report that mefloquine accumulation is undiminished in erythrocytes infected with P. berghei CR. Mefloquine is a new antimalarial drug (15) that is more effective than chloroquine against P. berghei CR (16) and P. falciparum CR (1,13,(17)(18)(19)21).…”
mentioning
confidence: 99%